2015
DOI: 10.1158/1940-6207.capr-14-0245
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diindolylmethane Suppresses Inflammation-Driven Lung Squamous Cell Carcinoma in Mice

Abstract: Inflammatory conditions of the lung such as chronic obstructive pulmonary disease (COPD) are known to increase lung cancer risk, particularly lung squamous cell carcinoma (LSCC). In the present study, we developed a mouse model of inflammation-driven LSCC that was induced by N-nitroso-trischloroethylurea (NTCU) and enhanced by lipopolysaccharide (LPS), a potent proinflammatory agent contained in tobacco and tobacco smoke, and determined the chemopreventive effects of BioResponse diindolylmethane (DIM) in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…As far as we know, this was the first time to report inflammation‐related lung cancer model in vitro. Indeed, Song et al, established inflammation‐driven lung tumor mouse models using N‐nitroso‐trischloroethylurea (NTCU) or 4‐(methyl‐nitrosoamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK) and LPS, but these models were set up in vivo. However, in vitro model regarding the inflammation‐associated lung cancer was lacking, and our study provided a suitable model for exploring the mechanisms of inflammation‐related lung cancer in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as we know, this was the first time to report inflammation‐related lung cancer model in vitro. Indeed, Song et al, established inflammation‐driven lung tumor mouse models using N‐nitroso‐trischloroethylurea (NTCU) or 4‐(methyl‐nitrosoamino)‐1‐(3‐pyridyl)‐1‐butanone (NNK) and LPS, but these models were set up in vivo. However, in vitro model regarding the inflammation‐associated lung cancer was lacking, and our study provided a suitable model for exploring the mechanisms of inflammation‐related lung cancer in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the theory of “inflammation and cancer” has gradually attracted people's attention, and the inflammatory microenvironment has been regarded as “seventh hallmark of cancer.” Since lung is an organ that communicates directly with the outside world, it is easily exposed to environmental pollutants and pathogenic microorganisms to form inflammatory microenvironment . Although studies have confirmed that the sustained existence of chronic inflammation in the lung is a major driving force for the development of lung cancer, the molecular mechanism that chronic inflammation promotes lung cancer has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(510) Both I3C and DIM possess strong effects in vitro and in-vivo against cancers of the lung, colon, prostate, and breast. (11–14) Mice gavaged with NNK and then treated with I3C or DIM developed significantly fewer lung tumors compared to controls. (13, 15, 16) In a placebo-controlled clinical trial, I3C taken for 12 weeks resulted in regression of cervical intraepithelial neoplasia in approximately half of the 17 women randomized to either 200 mg or 400 mg daily compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genetically engineered mouse models have demonstrated that endogenous airway stem cells function as the cell-of-origin for murine lung cancer 3,12,13 . In these models, it is notable that the incidence, speed, and severity of lung tumours are all increased following lung injury and the presence of a pro-inflammatory microenvironment 14,15 . These results suggest that conserved, endogenous signalling pathways responsible for lung injury outcomes may additionally regulate lung tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%